Ultrasound-Guided Cannulation of the Great Saphenous Vein in Neonates: A Randomized Study - Tu, Zhenzhen; Tan, Yanzhe; Liu, Lifei; Xie, Jia; Xu, Ying; Liu, Wei (American Journal of Perinatology, 2021)
Objective This prospective randomized controlled study aimed to compare the ultrasound-guided (USG) technique with the standard single-wall puncture technique for epicutaneo-caval catheter (ECC) placement in neonates.Study Design A total of 100 neonates were included in this study. All enrolled neonates were randomly divided into two groups (n = 50): the USG group and the control group. The control group underwent standard single-wall puncture for ECC placement procedures, and the USG group underwent USG ECC placement procedures.Results The first attempt success rates (62 vs. 38%; p = 0.016) and the total success rates (92 vs. 74%; p = 0.017) were higher in the USG group than in the control group. The procedure time was shorter in the USG group than in the control group: 351.43 (112.95) versus 739.78 seconds (369.13), p < 0.001. The incidence of adverse events was not significantly different between the two groups.Conclusion Compared with the standard single-wall puncture method, USG cannulation is superior for neonatal ECC placement, with a higher success rate, and decreases the total procedural time.Key Points
Keywords: ultrasound guided; epicutaneo-caval catheters; neonates; cannulation; great saphenous vein